2017
DOI: 10.3390/catal7110343
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning Synthesis and Characterization of Mono-Sized H-Beta Zeolite-Supported Palladium-Iridium Nanoparticles and Application in the Selective Hydrogenation of Acetylene

Abstract: Abstract:In this research, a mono-sized Beta zeolite support synthesized by the solvothermal method was used in the selective acetylene to ethylene hydrogenation reaction with minimum coke build up on the catalyst surface. Tetrapropylammonium hydroxide (TPAOH), tetrapropylammonium bromide (TPABr), n-butylamine, and morpholine were used as structure direct agents (SDA) in the support to obtain various shapes. The characterization results show that although the Si/(Al + SDA) ratio has no effect on the phase puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…A narrow loop of type II isotherm was observed with HBZ, which confirms the formation of a well-ordered microporous structure with uniform pore size distribution (Barata-Rodrigues et al, 2003 ). The significant reduction in the amount of nitrogen adsorbed in both monolayer and the multilayer region confirms the formation of small pore size and lesser surface area (Sahooli et al, 2017 ). The capillary condensation step, which gives the direct measure of the pore diameter of the materials, has shifted towards the low relative pressure for HBZ revealing a reduction in the pore diameter of around 5 A 0 (Figure 2c ; Sahooli et al, 2017 ).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…A narrow loop of type II isotherm was observed with HBZ, which confirms the formation of a well-ordered microporous structure with uniform pore size distribution (Barata-Rodrigues et al, 2003 ). The significant reduction in the amount of nitrogen adsorbed in both monolayer and the multilayer region confirms the formation of small pore size and lesser surface area (Sahooli et al, 2017 ). The capillary condensation step, which gives the direct measure of the pore diameter of the materials, has shifted towards the low relative pressure for HBZ revealing a reduction in the pore diameter of around 5 A 0 (Figure 2c ; Sahooli et al, 2017 ).…”
Section: Resultsmentioning
confidence: 78%
“…The significant reduction in the amount of nitrogen adsorbed in both monolayer and the multilayer region confirms the formation of small pore size and lesser surface area (Sahooli et al, 2017 ). The capillary condensation step, which gives the direct measure of the pore diameter of the materials, has shifted towards the low relative pressure for HBZ revealing a reduction in the pore diameter of around 5 A 0 (Figure 2c ; Sahooli et al, 2017 ). Zhang et al ( 2013 ) also reported similar physical characteristics for HBZ.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The XRD patterns in Figure 2a,b show that the intensities of the signal peaks at (004) and (302) corresponding to the crystal planes of Hβ-30 zeolite varied in the following order: 1,4-dioxane > THF > GVL > MIBK > DMSO > ACE > DMF > H 2 O. 40,41 All of the signal peaks of Hβ-30 zeolite after 1,4-dioxane treatment had almost the same intensities as the fresh one, whereas the (004) crystal plane was close to disappearing after treatment in DMF, ACE, and water. Furthermore, the effect of the solvent on the acidity of Hβ-30 zeolite was analyzed by Py-FTIR (Figure 2c).…”
Section: Solvent Effect On Furfural Production Over Hβ Zeolitementioning
confidence: 99%